Islamic Organizational Culture, Islamic Work Ethics and Job Satisfaction’s Impact on Employee Performance in Islamic Microfinance - Naila Mufawazah; Mahmudatus Sadiyah (Mutanaqishah: Journal of Islamic Banking, 2025)
Purpose – The purpose of this study is to examine the effect of Islamic work ethic, Islamic organizational culture, and job satisfaction on the employee performance of BMT under ASKOWANU Jepara. The Islamic microfinance in this study is BMT ASKOWANU Jepara. Methodology – This research used a quantitative methodology and a sample of 80 employees at BMT affiliated with ASKOWANU Jepara. The data was collected utilizing a purposive sampling method and a questionnaire. Data analysis methodologies encompass ordinary least squares (OLS) regression and hypothesis testing, namely the partial test (T test) and simultaneous test (F test). Findings – The results indicated that Islamic organizational culture influences employee performance at BMT Jepara. Nonetheless, the Islamic work ethic and job satisfaction exert no influence on employee performance. Implications – These studies offer guidance for BMT managers to enhance Islamic work ethic and workplace happiness to elevate staff performance. A more effective technique is required for achieving the adoption of Islamic organizational culture within the workplace. Originality – This study provides empirical insights into the correlation among Islamic work ethic, Islamic organizational culture, and job satisfaction inside Islamic microfinance institutions, specifically BMTs in Jepara, utilizing a quantitative method.